EFEKTIVITAS IMPLEMENTASI STANDAR KINERJA SDM SEBAGAI PENDUKUNG ISO 9001 : 2008 TERHADAP KUALITAS PELAYANAN PUBLIK DI PUSKESMAS II DENPASAR SELATAN - Septiarini Susanti, Ari (CITIZEN CHARTER, 2014)
ABSTRACT The aim of the present study was to investigate the implementation of effective Human Resource (HR) Performance Standard on the Quality of Public Services in Health Center of Densel II, South Denpasar. This study made use quantitative research methods. The data collection method used in this study was questionnaire method. Furthermore, based on the research results for the 6 indicators of performance standards by Russel and 5 indicators of services quality by Parasuraman et al., showed that the implementation of effective Human Resource (HR) Performance Standards as a supporting ISO 9001 : 2008 effective or had a positive and significant effect on the Quality of Public Services in Health Centers of Densel II, South Denpasar. Â  Keywords: Performance Standards, ISO 9001:2008, Quality Services Â